Fishers of men the missionary influence of an extended family in Central Africa - Summerton, Pauline; Brethren Archivists and Historians Network (Brethren Archivists and Historians Network, 2003)
Includes bibliographical references, index, maps, diagrams
Brethren writer
Keywords: Brethren movement -- missions -- Central Africa